SAA الإدارة الالكترونية للمعلومات في قطاع التامين الجزائري دراسة حالة الشركة الوطنية للتامين - منصور، منال; فرحات، عبد الكريم (University Of Eloued جامعة الوادي, 2024)
يهدف البحث الى تحديد مدى فعالية وكفاءة الإدارة الإلكترونية في شركات التامين الجزائرية، وإبراز الانعكاسات الايجابية التي يقدمها كآداة مهمة تضمن سير العمليات التقنية للتامين، التامين المشترك وإعادة التامين، من خلال دراسة ميدانية داخل الشركة الوطنية للتأمين، خلال الفترة 2020-2023، باعتبارها الرائدة في القطاع منذ سنوات من خلال رقم أعمالها، من جهة، والسباقة في تبني مثل هذه الأنظمة، من جهة ثانية.خلص البحث الى عدة نتائج أكد معظمها يؤكد الدور الإيجابي لتبني أنظمة الإدارة الإلكترونية المتعددة على مستواها، من خلال محافظتها على الريادة، وارتفاع قيمة رقم أعمالها وحصتها السوقية، لهذا أوصى البحث بضرورة تقوية هذه الأنظمة حسب الحجم المالي للشركة والتموضع الجغرافي لفروعها لتكون على إطلاع واسع بما يجري داخلها. Abstract: The research aims to determine the effectiveness and efficiency of electronic management in Algerian insurance companies, Highlighting the positive repercussions that it provides as an important tool that ensures the smooth running of technical operations for insurance, co-insurance and reinsurance, Through a field study within the National Insurance Company, during the period 2020-2023, As a leader in the sector for years through its turnover, on the one hand, and a pioneer in adopting such systems, on the other hand. The research concluded with several results, most of which confirm the positive role of adopting multiple electronic management systems at their level, By maintaining its leadership and increasing the value of its turnover and market share, the research recommended the necessity of strengthening these systems according to the financial size of the company and the geographical location of its branches so that they are widely informed of what is happening within them.
Electronic information management in the Algerian insurance sector, a case study of the National Insurance Company SAA
مداخلة
Keywords: الإدارة الإلكترونية; نظام المعلومات الإلكتروني; شركات التامين الجزائرية; الشركة الوطنية للتأمين; الجزائر; Electronic management; Electronic information system; Algerian insurance companies; National Insurance Company; Algeria